Aloestratigrafia e análise de fácies: "revoluções" na geologia sedimentar e o estudo do quaternário - Mello, Claudio Limeira (Anuário do Instituto de Geociências, 1994)
A conceptual discussion is presented concerning some important aspects of the modern sedimentary geology as they are related to particularities of the Quaternary sedimentary record. This study intends to provide new elements for a most objective analysis of Quaternary deposits. The approach utilized is based on the purpose to integrate stratigraphie and sedimentologic analysis. The allostratigraphic perspective and the faciologic analysis of events are hereby recommended. The association of geomorphology and stratigraphy is also emphasized as a basic aspect to studies of Quaternary deposits. Concerning this aspect, the identification of depositional surfaces is particularly important.